The Case for Global Fiscal Stimulus - Lee, Jaewoo (IMF Staff Position Notes; Staff Position Note ;, 2009)
This paper presents simulations with a multicountry structural model to show that worldwide expansionary fiscal policy combined with accommodative monetary policy can have significant multiplier effects on the world economy. It also provides a framework for assessing the effects of fiscal actions needed to help counter the projected contractionary pressures in the world economy. In an ideal scenario where fiscal stimulus is both global and supported by monetary accommodation, and where financial sectors that are under pressure are being supported by governments, every dollar spent on government investment can increase GDP by about USD 3, while every dollar of targeted transfers can increase GDP by about USD 1. In countries in which fiscal space is limited, it will be especially important to focus fiscal stimulus actions on those measures that will have the largest effect on aggregate demand. It is particularly important for fiscal policy to take on an increased share of the burden during the period in which the financial sector is recovering and is not yet able or willing to extend credit to households and businesses to the extent that it normally does.